2016
DOI: 10.2147/ott.s113606
|View full text |Cite
|
Sign up to set email alerts
|

Association of preoperative levels of selected blood inflammatory markers with prognosis in gliomas

Abstract: BackgroundRed cell distribution width (RDW), neutrophil–lymphocyte ratio (NLR), and platelet count (PLT) routinely tested as part of the complete blood count are indicative of systemic inflammation. The prognostic significance of NLR and PLT in cancer was demonstrated in many studies while the role of RDW has been hardly investigated. The present study aimed to assess the association of RDW, NLR, and PLT with survival and tumor grade in glioma patients.MethodsClinical data from 178 patients with primary glioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
63
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 26 publications
3
63
1
4
Order By: Relevance
“…Moreover, NLR was a prognostic marker in gliomas, which was consistent with findings in multiple other solid tumors . Using a cutoff NLR value of four, Raushan auezova et al reported on the associations of NLR with OS in 178 patients and Jing Zhang et al demonstrated that higher NLR was correlated with shorter OS. In our study, we found that the OS of patients in NLR >3.2 group was significantly shorter than in NLR <3.2 group.…”
Section: Discussionsupporting
confidence: 70%
“…Moreover, NLR was a prognostic marker in gliomas, which was consistent with findings in multiple other solid tumors . Using a cutoff NLR value of four, Raushan auezova et al reported on the associations of NLR with OS in 178 patients and Jing Zhang et al demonstrated that higher NLR was correlated with shorter OS. In our study, we found that the OS of patients in NLR >3.2 group was significantly shorter than in NLR <3.2 group.…”
Section: Discussionsupporting
confidence: 70%
“…suggested that PLR could be a diagnostic value in different metastasis from GBM. Preoperative RDW and PNI levels are also beneficial to evaluate glioma outcomes . Inversely, Diaz and his colleague have reported that pretreatment systemic inflammatory markers (NLR, MLR, and PLR) are not associated with improved OS in patients with GBM.…”
mentioning
confidence: 99%
“…Абсолютное и относительное содержание клеток врожденного и приобретенного иммунитета в периферической крови уже используют для прогнозирования длительности периода ремиссии при некоторых онкологических заболеваниях, в част-ности, опухолях пищевода, яичников, желудка [8][9][10][11]. При глиобластомах при сотношении НГ/Лф больше 4 деятельность послеоперационной ремиссии превыша-ла 11 мес [12,13]. В то же время, содержание в крови клеток врожденного и приобретенного иммунитета при многих опухолях, в том числе опухолях мозга различного происхождения и степени анаплазии, недостаточно изучено, а прогностическая ценность предлагаемых показателей спорна [5,14,15].…”
Section: вміст клітин вродженого та набутого імунітету у периферійнійunclassified
“…Рост опухолей нейро-эктодермального и мезенхимального происхождения сопровождался изменением как количества, так и соотношения клеток врожденного и приобретенного иммунитета, что согласуется с данными об иммуно-супрессии Т-клеточного звена иммунитета, а также воспалительной реакциеи в опухолевом очаге [1][2][3][4]. В отличие от ряда других опухолей человека, в частнос-ти, яичников, легких, желудка [5,9,11,15], для которых показательным является изменение количества Тр, для опухолей головного мозга характерно соотношение НГ/Лф, соответствующее большей прогностической ценности и информативности при глиобластомах [12,13] колоректальном раке [14].…”
Section: український нейрохірургічний журнал 2017;(4):38-41unclassified